EFEKTIFITAS MEDIASI DALAM PENYELESAIAN PERKARA PERCERAIAN DI PENGADILAN AGAMA PADANG - Miasiratni, Miasiratni; Agustini, Sri; Harniwati, Harniwati (Ensiklopedia of Journal, 2026)
This study aims to analyze the effectiveness of mediation in resolving divorce cases at the Padang Religious Court. The method used was an empirical method with a qualitative-descriptive approach. Data were collected through in-depth interviews with judges, mediators, and the parties involved in the divorce process, as well as through a study of case decision documents. Data analysis was conducted descriptively to describe the mediation process and outcomes. The results indicate that mediation at the Padang Religious Court is quite effective in fostering amicable agreements, although obstacles remain, such as unpreparedness of the parties and limited mediation time. This study provides an overview of the importance of mediation as an alternative for resolving divorce disputes and serves as a reference for developing mediation practices in religious courts. Keywords: mediation, divorce, Religious Court, effectiveness, case resolution